The technological influence on health professionals' care: translation and adaptation of scales - Carlos Manuel Torres Almeida; Filipe Nuno Alves dos Santos Almeida; Joaquim José Jacinto Escola; Vitor Manuel Costa Pereira Rodrigues (Universidade de São Paulo, 2016)
Objectives: in this study, two research tools were validated to study the impact of technological influence on health professionals' care practice. Methods: the following methodological steps were taken: bibliographic review, selection of the scales, translation and cultural adaptation and analysis of psychometric properties. Results: the psychometric properties of the scale were assessed based on its application to a sample of 341 individuals (nurses, physicians, final-year nursing and medical students). The validity, reliability and internal consistency were tested. Two scales were found: Caring Attributes Questionnaire (adapted) with a Cronbach's Alpha coefficient of 0.647 and the Technological Influence Questionnaire (adapted) with an Alpha coefficient of 0.777. Conclusions: the scales are easy to apply and reveal reliable psychometric properties, an additional quality as they permit generalized studies on a theme as important as the impact of technological influence in health care.